2002
DOI: 10.1128/aem.68.11.5625-5633.2002
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Belonging to the Genus Cycloclasticus Play a Primary Role in the Degradation of Aromatic Hydrocarbons Released in a Marine Environment

Abstract: To identify the bacteria that play a major role in the aerobic degradation of petroleum polynuclear aromatic hydrocarbons (PAHs) in a marine environment, bacteria were enriched from seawater by using 2-methylnaphthalene, phenanthrene, or anthracene as a carbon and energy source. We found that members of the genus Cycloclasticus became predominant in the enrichment cultures. The Cycloclasticus strains isolated in this study could grow on crude oil and degraded PAH components of crude oil, including unsubstitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
121
1
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(132 citation statements)
references
References 51 publications
2
121
1
8
Order By: Relevance
“…PAHs Cycloclasticus [36,42,43,73] Pyrene Mycobacterium [25,41,72] one basking alkanes and phytane in 21 days was 47.29 and 41.21 %, respectively [64]. Yuan et al also found the degradation rate of branched hydrocarbons was nearly two times than that of n-alkanes hydrocarbons [77].…”
Section: The Degradation Rate Of Branched Hydrocarbons Is Significantmentioning
confidence: 99%
“…PAHs Cycloclasticus [36,42,43,73] Pyrene Mycobacterium [25,41,72] one basking alkanes and phytane in 21 days was 47.29 and 41.21 %, respectively [64]. Yuan et al also found the degradation rate of branched hydrocarbons was nearly two times than that of n-alkanes hydrocarbons [77].…”
Section: The Degradation Rate Of Branched Hydrocarbons Is Significantmentioning
confidence: 99%
“…Most hydrocarbonoclastic bacteria metabolize either aliphatic or aromatic hydrocarbons, although some bacteria such as strains of Pseudomonas (Whyte et al, 1997) and Rhodococcus (Andreoni et al, 2000) have been shown to degrade both types of hydrocarbons. Among hydrocarbonoclastic bacteria, Alcanivorax (Hara et al, 2003;Kasai et al, 2001;Roling et al, 2004;Yakimov et al, 1998Yakimov et al, , 2005 and Cycloclasticus (Dyksterhouse et al, 1995;Kasai et al, 2002a;Maruyama et al, 2003) strains have been identified as key micro-organisms in the degradation of aliphatic and aromatic hydrocarbons, respectively, in marine environments (Harayama et al, 2004). Alcanivorax strains are distributed in natural marine environments around the world .…”
Section: Introductionmentioning
confidence: 99%
“…Another characteristic of marine environments is that the vast majority of bacteria (90-99%) are uncultivable (Amann et al, 1995); hence, the analysis of microbial communities that contribute to in situ hydrocarbon biodegradation activities has been a challenge to microbiologists (Rollins & Colwell, 1986;Wilkinson 1988 Since the pioneering work on marine bacteria by C.E. ZoBell, many bacterial strains have been isolated from the coastal and oceanic environments; these bacteria, including the genera Alteromonas (Beckman et al, 2008;Ivanova et al, 2004), Aeromonas (Stabili & Cavallo 2004), Alcanovorax (Head et al, 2006;Purkrtova et al, 2010), Bacillus (Oguntoyinbo, 2006), Cycloclasticus (Kasai et al, 2002), Chromobacterium, Flavobacterium, Marinobacter spp., Shewanella (Holt et al, 2005), Microscilla (Lennon, 2007), Micrococcus (Süss et al, 2004), Rhodococcus (Süss et al, 2004), Photobacterium, Planacoccus, Pseudomonas, Pseudoalteromonas, and Vibrios, among other genera, have been considered to be representative of marine bacteria. Many of them have the capacity to use different hydrocarbons (Head et al, 2006, Yu et al, 2005a.…”
Section: Introductionmentioning
confidence: 99%